Health financing and budgeting practices for health in South Africa - James, Chris (OECD Publishing, 2018)
South Africa has made substantial progress in developing its health care system since 1994. Universal access is a fundamental principle of the Constitution and health sector policies, and health outcomes have improved on aggregate. However, health inequities remain an important challenge today. Focusing on public financial management and the budgeting process for health, South Africa has a clear, well-structured and transparent process to budget formulation from national to provincial governments. But this transparency does not fully transmit on allocation decisions to health from provincial treasuries. In terms of budget execution, up-to-date data reporting systems, strict enforcement of fiscal rules, and well-developed monitoring processes are good budgetary practices. However, despite good aggregate spending levels, there is great disparity in the way provinces execute their budget. Finally, South Africa has well-established monitoring processes. However, the link between performance indicators and the budget process remains limited and could be strengthened